Board of Directors, Audit Committee, Executive Compensation and Tax Avoidance of Banking Companies in Indonesia - Utami Nuur Lailatul Idzniah; Yustrida Bernawati (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2020)
Tax avoidance is the hottest issue in the last five years. It is reinforced with the Tax Amnesty Program by the Directorate General of Taxation (DJP), which began in June 2016. Therefore, this study aims to obtain empirical evidence of the influence of good corporate governance and executive compensation on corporate tax avoidance. This study used 215 banking companies listed on the Indonesia Stock Exchange (IDX) for 2014-2018. This study using a purposive sampling method that produced 119 suitable samples. The analytical method used is multiple linear regression analysis through IBM SPSS Statistics 25 software. Computation of tax avoidance is proxied by computing of Effective Tax Rates (ETR). Good corporate governance is proxied by the size of the board of directors and the audit committee, and executive compensation is proxied by all director compensations. The size of the audit committee is a total of the audit committee in one period. The size of the board of directors is the total of the board committee in one period. This study used ROA and Leverage as a control variable. In this study, it was found that executive compensation and good corporate governance, which was proxied by the Size of the board of directors and the Size of the audit committee shown a positive effect on tax avoidance. Investors who do not want tax avoidance must pay attention to executive compensation and good corporate governance in the company. In contrast, control variables have not significant effect on tax avoidance.